Quantitative nylon monomerization by the combination of chemical pretreatment and enzymatic hydrolysis using nylon hydrolases. - Yuki Shiraishi; Dai-Ichiro Kato; Kaito Miyazaki; Maina Yonemura; Yoko Furuno; Risa Yokoyama; Yukiko Yokogawa; Sho Nonaka; Yoshiro Kaneko; Keigo Ebata; Yuichiro Himeda; Seiji Negoro (PLoS ONE)
Nylons, derived from fossil fuels, are widely used for their toughness and flexibility, but they pose environmental concerns due to their low biodegradability. This study explored an efficient method for the monomerization of polymeric nylons, specifically nylon-6 and nylon-6,6, through a combination of chemical pretreatment and enzymatic hydrolysis using two kinds of nylon hydrolases, NylB and NylC (Nyl series enzymes). To break down the strong intermolecular hydrogen bonding between polymer chains of nylon, two pretreatment methods were investigated: homogeneous dispersion and soluble oligomerization induced by acid treatment. Homogeneous dispersion enhances water solubility, while soluble oligomerization reduces the molecular weight. These pretreatments significantly increased the enzyme sensitivity of the nylons, resulting in nearly complete conversion into monomers by Nyl series. Finally the convincing monomerization toward market products such as used fishing nets was also achieved. This study highlights the potential of this methodology for chemical recycling, offering a promising solution for reducing environmental impacts and achieving a circular economy for nylon products.